Studies in Australian Tettigoniidae: new Phaneropterine Katydids from Queensland Rainforests (Orthoptera: Tettigoniidae; Phaneropterinae) - Rentz, Dcf; Su, You Ning; Ueshima, Norhiro (Zootaxa, 2008)
New species of Phaneropterinae are described from the tropical rainforests of far north Queensland. A number of new species of the widespread Australian genus Caedicia (C. webberi, C. goobita and C. kuranda) are described with notes on biology and ecology. C. flexuosa I. Bolivar is recorded from Australia for the first time. Currimundria and Kurandoptera are described as new genera each with very distinctive species and a new species of Ephippithyta, E. kuranda, is also described from north Queensland. Two species of Diastella are described, D. kuranda and D. hilleri. One species of Diastella, D. hilleri, is described from the mountains of southeast Queensland. Cytological information is presented for several taxa. A key to the relevant Australian genera in the “Group” Ephippithytae is presented.